PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SMART BOX PADA MATA PELAJARAN IPAS UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV SEKOLAH DASAR - Feby Pelani Trisnawati; Ira Restu Kurnia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop smart box learning media as a teaching aid or learning tool to increase the motivation of fourth grade elementary school students to the value of the material currency. The development Model in this research is ADDIE (Analysis, Design, Development, Implementation, Evaluation) model with research subjects of fourth grade students. Data collection instruments include observation, interviews, expert validation questionnaires, teacher and student response questionnaires and pre-match and post-test learning motivation questionnaires. The results of the validation of the feasibility of material experts obtained 92.5%, media experts obtained 92.86%, and linguists obtained 95.83%. The results of the feasibility of teacher responses obtained by 95% and student responses obtained by 86.97%. While the N-Gain results obtained by 0.8 with high criteria and a percentage of 80%. The results of this study indicate that the smart box Learning media developed is very feasible and effective to improve the learning motivation of elementary school students.